Quality of brazilian beef exports: Analysis of recent data and regulatory challenges (Research, Society and Development, 2026)
Brazil is one of the leading exporters of beef in the international market, with China accounting for approximately 48% of the exported volume, followed by the United States, Chile, the European Union, Russia, and Mexico. This scenario highlights the strong dependence on the Chinese market, while also indicating the gradual diversification of destinations for Brazilian beef. The sector faces challenges related to tariff and non-tariff barriers, including strict sanitary requirements, traceability, and animal welfare standards. This study aimed to analyze the main markets for Brazilian beef, considering export performance, regulatory requirements, trade barriers, and sectoral trends. The research was based on a bibliographic and documentary survey, including data from the USDA, FSIS, MAPA, ABIEC, FAO, and RASFF, as well as academic articles addressing competitiveness and supply chain dynamics. The analysis indicated a reduction in RASFF alerts between 2024 and 2025, reflecting advances in food safety. However, the United States maintains significant tariff barriers, which negatively impact competitiveness. It was concluded that, although Brazil presents favorable conditions to maintain its international relevance in the sector, investments in traceability, technological innovation, sustainability, and market diversification are essential to expand access and consolidate its position in the global market.